The Implementation of Multistrategy Approach in Improving Arabic Language Skills at Medan Health Polytechnic Nursing - Kamalia, Kamalia (Arabiyatuna: Jurnal Bahasa Arab, 2024)
The research aimed to develop learning strategies that would meet the needs of nursing students through a multi-strategy approach. This study employed a quantitative method to measure the impact of the multi-strategy approach in learning Arabic at Medan Nursing Poltekkes. An experimental approach was utilized, with pre-test and post-test assessments administered to students using a questionnaire to test alternative hypotheses. Data from experiments and literature were analyzed using statistical tests such as T-Test. This study demonstrated that the multi-strategy approach led to a significant improvement in Arabic language skills among students at Medan Health Poltekkes, with the average skill level increasing to 96.85 from the previous 45.14. All students managed to reach the "complete" skill level, with 100% of the "very high" level. The significance test indicated that the difference between the pre-test and post-test had a very low significance value (0.000), underscoring the positive impact of this multi-strategy approach. The integration of online learning applications and multimedia provides variations in teaching methods and increase learning motivation, while the use of reading material that is relevant to the field of nursing and emphasis on Arabic literacy prepares students for the challenges of communication in the world of multicultural work. By integrating various learning methods such as multimedia, language games, and direct interaction with teaching material, students can develop speaking, listening, reading, and writing skills. Direct and dynamic interactions between teachers and students are also the key in deepening understanding and increasing self -confidence in using Arabic.